Global biogeography of SAR11 marine bacteria - Brown, MV; Lauro, FM; Demaere, MZ; Muir, L; Wilkins, D; Thomas, T; Riddle, M; Fuhrman, J; Andrews-Pfannkoch, C; Hoffman, JM; McQuaid, J; Allen, A; et al. (Molecular Systems Biology, 2012)
The ubiquitous SAR11 bacterial clade is the most abundant type of organism in the world's oceans, but the reasons for its success are not fully elucidated. We analysed 128 surface marine metagenomes, including 37 new Antarctic metagenomes. The large size of the dataset enabled internal transcribed spacer (ITS) regions to be obtained from the Southern polar region, enabling the first global characterisation of the distribution of SAR11, from waters spanning temperatures -2ºC to 30ºC. Our data show a stable co-occurrence of phylotypes within both "tropical" (>20ºC) and "polar" (